The Public Repercussions of Mandatory Audit Rotation and an Empirical Research in the UK Market - Sun, Ding (2006)
This paper focuses on the attitudes of public companies to the mandatory auditor rotation, especially mandatory audit firm rotation. The existing literatures and important empirical studies, mainly referring to the advantages and disadvantages of mandatory auditor rotation, are reviewed and discussed in detail. A quantitative research is performed to exam the characteristics of companies that switch audit firms on the UK market. It finds that the UK public hold positive attitudes to mandatory audit firm rotation, and the mandatory rotation may lead to more audit failures.